The mediating effects of parental self-efficacy and parental involvement on the link between family socioeconomic status and children's academic achievement. Issue 3 (3rd July 2019) - Tazouti, Youssef; Jarlégan, Annette
ABSTRACT: The present study examined the hypothesis that parental self-efficacy and parental involvement in children's education mediate the link between family socioeconomic status and children's academic achievement. We used a multidimensional approach and a structural equation model combining all the study variables to test our hypothesis on both mothers and fathers. Our research examined 203 parents and their children attending the first or second year (CE1 or CE2) of elementary school in seven different schools. This is the first study of its type to be carried out on a sample of French families. Results for the mothers support our main hypothesis of a mediating effect of parental self-efficacy and parental involvement on children's academic achievement. However, our hypothesis was not supported in the case of the fathers and we noted several differences between mothers and fathers.